Use of outpatient care in VA and Medicare among disability-eligible and age-eligible veteran patients - Liu Chuan-Fen; Bryson Chris L; Burgess James F; Sharp Nancy; Perkins Mark; Maciejewski Matthew L (BMC, 2012)
Abstract Background More than half of veterans who use Veterans Health Administration (VA) care are also eligible for Medicare via disability or age, but no prior studies have examined variation in use of outpatient services by Medicare-eligible veterans across health system, type of care or time. Objectives To examine differences in use of VA and Medicare outpatient services by disability-eligible or age-eligible veterans among veterans who used VA primary care services and were also eligible for Medicare. Methods A retrospective cohort study of 4,704 disability- and 10,816 age-eligible veterans who used VA primary care services in fiscal year (FY) 2000. We tracked their outpatient utilization from FY2001 to FY2004 using VA administrative and Medicare claims data. We examined utilization differences for primary care, specialty care, and mental health outpatient visits using generalized estimating equations. Results Among Medicare-eligible veterans who used VA primary care, disability-eligible veterans had more VA primary care visits (p < 0.001) and more VA specialty care visits (p < 0.001) than age-eligible veterans. They were more likely to have mental health visits in VA (p < 0.01) and Medicare-reimbursed visits (p < 0.01). Disability-eligible veterans also had more total (VA+Medicare) visits for primary care (p < 0.01) and specialty care (p < 0.01), controlling for patient characteristics. Conclusions Greater use of primary care and specialty care visits by disability-eligible veterans is most likely related to greater health needs not captured by the patient characteristics we employed and eligibility for VA care at no cost. Outpatient care patterns of disability-eligible veterans may foreshadow care patterns of veterans returning from Afghanistan and Iraq wars, who are entering the system in growing numbers. This study provides an important baseline for future research assessing utilizations among returning veterans who use both VA and Medicare systems. Establishing effective care coordination protocols between VA and Medicare providers can help ensure efficient use of taxpayer resources and high quality care for disabled veterans.